2018
DOI: 10.1093/ageing/afy092
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of older people’s patient and public involvement in health and social care research: a systematic review

Abstract: evidence for the impacts of older people's involvement is mixed although benefits appear to outweigh the challenges. Future considerations for PPI include matching older people's skills and motivations to the project and level of involvement, and establishing an iterative research process in which evaluation is embedded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
85
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 21 publications
2
85
0
1
Order By: Relevance
“…According to Cook et al (2017), not all change is measurable; a positive or awkward interaction can have a strong impact on people individually or the entire group. In a recent systematic review, Baldwin et al (2018) report that evidence of the impact is mixed, but the benefits of involvement seem to outweigh the challenges. We support their suggestion to embed evaluation in the iterative process of participatory research, in order to capture the meaning it has for the persons who are involved.…”
Section: Introductionmentioning
confidence: 99%
“…According to Cook et al (2017), not all change is measurable; a positive or awkward interaction can have a strong impact on people individually or the entire group. In a recent systematic review, Baldwin et al (2018) report that evidence of the impact is mixed, but the benefits of involvement seem to outweigh the challenges. We support their suggestion to embed evaluation in the iterative process of participatory research, in order to capture the meaning it has for the persons who are involved.…”
Section: Introductionmentioning
confidence: 99%
“…In a review on the impact of involving older adults in research that encompassed 30 studies, most studies did not give further participant details other than that the participants were aged 50+ (Fudge et al, 2007). In another review that encompassed nine studies, older adults as co-researchers were seen in some of the studies to have experience from the area being studied or had old-age-related conditions, but most studies did not give further participant details (Baldwin, Napier, Neville and Wright-St Clair, 2018). Baldwin et al found that older co-researchers experienced both benefits and challenges when participating in research: psychological and social benefits, new learning, activism and career opportunities but also demanding workloads, difficult relationships and dissatisfaction with the level of involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Baldwin et al found that older co-researchers experienced both benefits and challenges when participating in research: psychological and social benefits, new learning, activism and career opportunities but also demanding workloads, difficult relationships and dissatisfaction with the level of involvement. Academic researchers who included older co-researchers in their research experienced new learning and shared workloads, but also demanding workloads and difficult relationships (Baldwin et al, 2018). In their review, Fudge et al found anecdotal evidence that the involvement of older adults as co-researchers resulted in changes on the individual level but found little evaluation of how such involvement changed research processes or outcomes (Fudge et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The review found only four studies which formally evaluated involving older people in the research studies using different evaluation methods ranging from questionnaire to an ethnographic approach. A recent systematic review evaluated the impacts of involving older adults in health and social care research on older co-researchers, academic researchers and research processes 28 . The review analysed nine articles using a qualitative methodology evaluating older adults' involvement in research.…”
Section: Introductionmentioning
confidence: 99%